O corpo feminino como objeto de consumo e os modos de subjetivação na contemporaneidade - FONTINELE, Thaís Pinto (2020)
This study aims to discuss the subjectivation modes in relation to the female body in contemporary times, which is permeated by the sign of consumption. Therefore, the main objective of this study is to analyze the forms of agency of female bodies in contemporary scene, reiterated through disciplinary and control practices. For that, in the midst of gender discussions, I reflected on the relationship that is established between the construction of female identity, the norms related to body appearance and the capitalist interests that organize this social gear. I undertook a theoretical study, based on the genealogical perspective, aiming to understand the power games that build the notion of truth about the standards of femininity and beauty in consumer society. Starting from the analysis of resistance processes developed in profiles of the social network Instagram, I sought to problematize how the discursive practices that make possible the construction of the female gender are based on aesthetic and health representations that converge in a detailed norm, that of body adaptation to the market referents. Thinking subjectivity as a historical construction, I treated resistances as a force that opposes disciplinary power, such as a refusal to normative ideals, and which aim to compose new strategies for constituting oneself, more singular and freed. Keywords: